International Consortium of Vascular Registries Consensus Recommendations for Peripheral Revascularisation Registry Data Collection. (August 2018) - Behrendt, Christian-Alexander; Bertges, Daniel; Eldrup, Nikolaj; Beck, Adam W.; Mani, Kevin; Venermo, Maarit; Szeberin, Zoltán; Menyhei, Gabor; Thomson, Ian; Heller, Georg; Wigger, Pius; Danielsson, Gudmundur; et al.
Abstract : Objective/Background: To achieve consensus on the minimum core data set for evaluation of peripheral arterial revascularisation outcomes and enable collaboration among international registries. Methods: A modified Delphi approach was used to achieve consensus among international vascular surgeons and registry members of the International Consortium of Vascular Registries (ICVR). Variables, including definitions, from registries covering open and endovascular surgery, representing 14 countries in ICVR, were collected and analysed to define a minimum core data set and to develop an optimum data set for registries. Up to three different levels of variable specification were suggested to allow inclusion of registries with simpler versus more complex data capture, while still allowing for data aggregation based on harmonised core definitions. Results: Among 31 invited experts, 25 completed five Delphi rounds via internet exchange and face to face discussions. In total, 187 different items from the various registry data forms were identified for potential inclusion in the recommended data set. Ultimately, 79 items were recommended for inclusion in minimum core data sets, including 65 items in the level 1 data set, and an additional 14 items in the more specific level 2 and 3 recommended data sets. Data elements were broadly divided into (i) patient characteristics; (ii) comorbidities; (iii) current medications; (iv) lesion treated; (v) procedure; (vi) bypass; (vii) endarterectomy (viii) catheter based intervention; (ix) complications; and (x) follow up. Conclusion: A modified Delphi study allowed 25 international vascular registry experts to achieve a consensus recommendation for a minimum core data set and an optimum data set for peripheral arterial revascularisation registries. Continued global harmonisation of registry infrastructure and definition of items will overcome limitations related to single country investigations and enhance the development of real world evidence.